2019
DOI: 10.1039/c8ta12405a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, auxetic and strain-tunable two dimensional penta-X2C family as water splitting photocatalysts with high carrier mobility

Abstract: Penta-X2C (X = P, As and Sb): a novel two dimensional family for photo-catalytic water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 73 publications
4
45
0
2
Order By: Relevance
“…The Poisson's ratio of ZrS2 monolayer is somewhat smaller compared to MoS2 monolayer with ν =0.2 [34], which implies a higher potential for the application of ZrS2 monolayer than MoS2 in strain engineering applications. Graphically, the Poisson's ratio in all directions of the ZrS2 monolayer resembles a four-leaf clover, similar to the butterfly-shaped Poisson's ratio of the Penta-X2C family the previous report [35].…”
Section: Anisotropy Of Young's Modulus and Poisson's Ratiosupporting
confidence: 83%
“…The Poisson's ratio of ZrS2 monolayer is somewhat smaller compared to MoS2 monolayer with ν =0.2 [34], which implies a higher potential for the application of ZrS2 monolayer than MoS2 in strain engineering applications. Graphically, the Poisson's ratio in all directions of the ZrS2 monolayer resembles a four-leaf clover, similar to the butterfly-shaped Poisson's ratio of the Penta-X2C family the previous report [35].…”
Section: Anisotropy Of Young's Modulus and Poisson's Ratiosupporting
confidence: 83%
“…In addition, several other 2D materials have been theoretically predicted to exhibit photocatalytic activity for water splitting. [27,28,29,30,31,32,33,34,35,36,37,38,39,40] Binary IV-V compounds with the chemical formulas of IVV (GeP, GeAs, SiP, SiAs), [41,42] IVV2 ,(SiP2 , SiAs2 , GeP2 , GeAs2 ) [43,44,45,32] IVV3 (GeP3 ,SnP3 ), [42,46] and IVV5 (GeP5 ), [47] are emerged as another interesting class of semiconducting 2D materials. Our literature review have shown that IVV, IVV2, and IVV3 compounds exhibit polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…The results exhibit that these two materials show magical mechanical properties and can be used as interesting nano-auxetic materials, such as penta-graphene ( v = −0.068). 16 For verification, 25–28,47–50 we compare the response of NPR materials and PPR materials under different strains. Then, we apply uniaxial strain from −8% to 8% in the x direction to Penta-C 4 P 2 , Penta-C 2 Al 4 , and Penta-C 2 Ga 4 (since their structures coincide in the x and y directions, it is sufficient to consider only one of the directions).…”
Section: Properties Of Penta-cnx6−nmentioning
confidence: 99%
“…and Zn/Cd), Penta-X 2 C (X = P, As, Sb), penta carbides, and Penta-PdS 2 . 25–28 In conclusion, these stable pentagonal structures are sure to shine because of their unique electronic properties and potential applications.…”
Section: Introductionmentioning
confidence: 98%